Comparison Between Combined Scoring of Bethesda Cytology and TIRADS Ultrasound with Post- operative Histopathology in Thyroid Nodule - Karki, Reeba; Marasini, Anupama; Adhikari, Yuvraj; Bhandari, Shakar; Dutta, Vijay Bhushan; Mahaseth, Rajeev Kumar (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: A thyroid nodule is a discrete lesion within the thyroid gland that is radiologically distinct from the surrounding thyroid parenchyma. Thyroid ultrasonography is useful for risk stratification of nodules, and American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI-RADS) classification provides recommendations for fine-needle aspiration cytology (FNAC) based on objective ultrasonography features of these nodule. Methods: It is a prospective study conducted during the period of 8 months (June 2022- November 2022) Results Total 42 participants were included who visited ENT HNS outpatient department with thyroid nodules. Statistical Analysis was done using SPSS version 25. Spearmans correlation coefficient was used to evaluate the correlation between Bethesda and TIRADS, Bethesda and histopathological reports and TIRADS and Bethesda system. The P value was set at < 0.05 for statistical significance. Histopathology reports following surgery showed more than half of the nodules as benign nodules. Bethesda have 76.19%, 71.42%, 72.72%, 75% of sensitivity, specificity, Positive predictive value, and Negative predictive value respectively for malignancy while that of TIRADS is 65%, 68.18%, 65%, 68.18% respectively. Conclusion: FNAC is more sensitive and specific for diagnosis of thyroid malignancy but histopathological examination remains the gold standard.